Isolation and Functional Characterization of MsFTa, a FLOWERING LOCUS T Homolog from Alfalfa (Medicago sativa) - Kang, Junmei (Int J Mol Sci, 2019)
The production of hay and seeds of alfalfa, an important legume forage for the diary industry worldwide, is highly related to flowering time, which has been widely reported to be integrated by FLOWERING LOCUS T (FT). However, the function of FT(s) in alfalfa is largely unknown. Here, we identified MsFTa, an FT ortholog in alfalfa, and characterized its role in flowering regulation. MsFTa shares the conserved exon/intron structure of FTs, and the deduced MsFTa is 98% identical to MtFTa1 in Medicago trucatula. MsFTa was diurnally regulated with a peak before the dark period, and was preferentially expressed in leaves and floral buds. Transient expression of MsFTa-GFP fusion protein demonstrated its localization in the nucleus and cytoplasm. When ectopically expressed, MsFTa rescued the late-flowering phenotype of ft mutants from Arabidopsis and M. trucatula. MsFTa over-expression plants of both Arabidopsis and M. truncatula flowered significantly earlier than the non-transgenic controls under long day conditions, indicating that exogenous MsFTa strongly accelerated flowering. Hence, MsFTa functions positively in flowering promotion, suggesting that MsFTa may encode a florigen that acts as a key regulator in the flowering pathway. This study provides an effective candidate gene for optimizing alfalfa flowering time by genetically manipulating the expression of MsFTa.